Psychometric properties of the Brief-COPE for the evaluation of coping strategies in the Chilean population - García,Felipe E. (2018)
Abstract The Brief-COPE is an abbreviated version of the COPE (Coping Orientation to Problems Experienced) Inventory, a self-report questionnaire developed to assess a broad range of coping responses. Currently, it is one of the best validated and most frequently used measures of coping strategies. The aim of this study was to validate a culturally appropriate Chilean version of the Brief-COPE, assess its psychometric properties and construct and congruent validity. The Spanish version of the Brief-COPE was administrated in a community sample of 1847 Chilean adult (60.4% women) exposed to a variety of stressful experiences. The factorial structure of the inventory was examined by comparing four different models found in previous studies in Latin American population. The results of confirmatory factor analyses revealed, as in the original studies, a 14-factor structure of the Brief-COPE. These dimensions showed adequate internal structure and consistency. The factorial invariance comparing women and men confirmed strict invariance. Additionally, the results showed significant correlation between some Brief-COPE scales, such as denial and substance use, with perceived stress and emotional support and active coping with subjective well-being. Overall, the present work offers a valid and reliable tool for assessing coping strategies in the Chilean population.